Estrategias de publicidad del minimarket “Cesarin” de la ciudad de Babahoyo - Cambo Aspiazu, Jomaira Maricela (2022)
The "Cesarin" Minimarket, is a commercialization company of basic necessities, which is located in the City of Babahoyo, this is the object of study on advertising strategies implemented with the objective of knowing the positioning in the market and the capture of clients, in order to improve or innovate them with the intention of improving the commercial situation and image of the company, analyzing the strengths, weaknesses, opportunities and threats that it may have at the time of developing its activities, in addition to knowing how the customers perceive the advertising environment. The methodology that this case study holds is composed of the type of descriptive research, using the inductive method and data collection techniques such as survey and interview, with the intention of obtaining important data from the company in the surrounding area. . The results derived from the investigation show difficulties in the positioning of the company in the market since the marketing and advertising area is not fulfilling its functions adequately and in the current social and commercial context.